Representasi Kenakalan Remaja dalam Film Galaksi (Analisis Semiotik Model Charles Sanders Pierce pada Film “Galaksi”) - Galih Ridho Ibrahim; Urip Mulyadi (Universitas Serambi Mekkah, 2025)
The objective of this study is to identify and analyze the elements of signs used in the film Galaksi to depict juvenile delinquency, employing Charles Sanders Peirce's semiotic theory. This research adopts a qualitative approach with a semiotic analysis method focusing on three types of signs: icons, indices, and symbols. The subject of the study is the film Galaksi (2023), which explores the theme of juvenile delinquency against the backdrop of high school students' lives. The findings reveal that the film represents various forms of juvenile misconduct, such as safety violations (riding without a helmet), cyberbullying, inter-gang conflicts, and truancy. Through an analysis of visual and verbal signs, the study demonstrates that each element reflects the social and psychological dynamics of adolescents, ranging from rebellion against norms to efforts toward positive transformation.The results also highlight that the film does not merely portray negative adolescent behavior but underscores the significance of social support in the process of character transformation, particularly through the relationship between the main characters, Galaksi and Kejora. This study contributes valuable insights into how mass media, especially films, are utilized to represent social issues among adolescents.